Linking Management Behavior to Ethical Philosophy—An Empirical Investigation - Fritzsche, David J.; Becker, Helmut (Academy of Management Journal, 1984)
Ethical theory is linked to management behavior by classifying responses of managers to a series of vignettes according to the ethical theory represented by the response. The vignettes represent ethical dilemmas in the following areas: (I) coercion and control, (2) conflict of interest, (3) physical environment, (4) paternalism, and (5) personal integrity.